Effect of storage conditions and duration of erythrocyte mass and whole blood of dogs on mean erythrocyte volume and erythrocyte hemolysis - I. M. Yakymchuk (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
The study investigates the impact of storage conditions and duration on the mean corpuscular volume (MCV) and hemolysis levels of erythrocytes in canine whole blood and canine packed red blood cells (pRBC). The objects of the research were whole blood and pRBC obtained from healthy donor dogs and stored in a blood bank for 28 days. The results demonstrated significant morphological changes in erythrocytes during storage. Specifically, the MCV gradually increased, indicating membrane damage, dysfunction of the Na-K pump, and intracellular fluid accumulation. The increase in MCV was more pronounced in erythrocytes from whole blood compared to pRBC. This growth in MCV may reflect changes in erythrocyte shape, leading to impaired rheological properties and an elevated risk of microcirculatory thrombosis in recipients. The hemolysis level of erythrocytes also rose with longer storage durations. In whole blood, this parameter exceeded 1 % as early as the 14th day of storage, whereas in canine pRBC such a level was observed only on the 28th day. According to human blood standards, this level of hemolysis is critical and necessitates product disposal. The study also found that separating whole blood into components reduces the intensity of hemolysis, which could optimize blood storage practices in veterinary transfusion medicine. The research emphasizes the need to establish clear standards for storing canine blood products, taking into account storage duration and morphological changes in erythrocytes. Specifically, it recommends shortening the storage time for whole blood and increasing the proportion of blood separation during donation. The findings aim to reduce complications during transfusions in veterinary practice, thereby improving their efficacy and safety.